BRAND IMAGE SEBAGAI MEDIASI PENGARUH PROMOSI, HARGA DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN JAMU NYONYA MENEER DI SEMARANG TIMUR - Purnamasari, Sinta; Murwatiningsih, Murwatiningsih (Management Analysis Journal, 2015)
This research aims to know the existence of pricing and promotion, influence the attitude of consumers against purchasing decisions through the brand image as intervening variable. The population of this research is that consumers do purchase decisions helbal medicine outlets Nyonya Meneer in East Semarang. Sampling by using acidental sampling technique, the number of respondents were 116 respondents. Data collection method used is the method of observation, and a questionnaire method. Path analysis Analyse the data using SPSS version 16. These results indicate that the promotions significantly influence purchase decisions through brand image for a total impact for 0.502, significantly influence the price of purchaseÂ  decisions through the brand image for a total of 0.421 and significantly influence the consumer attitudes of purchaseÂ  decisions through the brand image for a total of 0.214. The conclusions of this study proved that the brand image has a role as an intervening variable between promotions, price and consumer attitudes to purchase decisions. Â